The liability of multinational companies through transnational litigation: comparative study of highlighted cases - Marullo, Maria Chiara; Esteve-Moltó, José Elías; Zamora-Cabot, Francisco Javier (Iberoamerican Journal of Development Studies, 2022)
Transnational litigation on business and human rights has grown exponentially in recent years and is playing a central role in the fight against impunity for serious human rights violations and environmental damage. We are witnessing a paradigm shift in the fight against corporate impunity, in which access to justice for victims is prioritized; also, in cases where it is not guaranteed before the judicial headquarters of the place where the mentioned violations were perpetrated. In our study, it is aimed to develop a critical and comparative legal analysis of the most recent and important jurisprudential developments and, particularly, but not in exclusive, from the Nevsun, Nestlé, Shell, and Vedanta cases, even the one that concerns the rights of the Waorani indigenous community.